N-Terminal Pro-B Type Natriuretic Peptide is Associated with Mild Cognitive Impairment in the General Population. - Kara, Kaffer; Mahabadi, Amir Abbas; Weimar, Christian; Winkler, Angela; Neumann, Till; Kälsch, Hagen; Dragano, Nico; Moebus, Susanne; Erbel, Raimund; Jöckel, Karl-Heinz; Jokisch, Martha (J Alzheimers Dis, 2017)
BACKGROUND: N-terminal pro-B type natriuretic peptide (NT-proBNP) is a marker of cardiac stress and is linked with silent cardiac diseases. While associations of cognitive impairment with manifest cardiovascular diseases are established, data on whether subclinical elevation of NT-proBNP levels below clinically established threshold of heart failure is related with cognitive functioning, especially mild cognitive impairment (MCI), is rare. OBJECTIVE: Aim of the present study was to investigate the cross-sectional association of NT-proBNP levels and MCI in a population-based study sample without heart failure. METHODS: We used data from the second examination of the population based Heinz-Nixdorf-Recall-Study. Subjects with overt coronary heart disease and subjects with NT-proBNP levels indicating potential heart failure (NT-proBNP≥300 pg/ml) were excluded from this analysis. Participants performed a validated brief cognitive assessment and were classified either as MCI [subtypes: amnestic-MCI (aMCI), non-amnestic-MCI (naMCI)], or cognitively-normal. RESULTS: We included 419 participants with MCI (63.1±7.4 y; 47% men; aMCI n = 209; naMCI n = 210) and 1,206 cognitively normal participants (62.42±7.1 y; 48% men). NT-proBNP-levels≥125 pg/ml compared to <125 pg/ml were associated with MCI in fully adjusted models (OR 1.65 (1.23;2.23) in the total sample, 1.73 (1.09;2.74) in men and 1.63(1.10;2.41) in women). For aMCI, the fully adjusted OR was 1.53 (1.04;2.25) and for naMCI, the fully adjusted OR was 1.34 (1.09; 166) in the total sample. CONCLUSION: Within normal ranges and without manifest heart failure, higher NT-proBNPlevels are associated with MCI and both MCI subtypes independent of traditional cardiovascular risk factors and sociodemographic parameters.